Analysing the Bit-error Probability of a receiver in Multi-User MIMO SC-FDMA systems - Kumar, Javalkar Dinesh; agarwal, Alok; Prasad, S.V.A.V (International Journal of Computer Sciences and Engineering, 2025)
SC-FDMA signals are currently espoused equally the Long Term Evolution (LTE) standard for the uplink due to its high data rate and low Peak to Average Power Ratio (PAPR). In SC-FDMA, two methods of choosing subcarriers for transmission are used; distributed using Interleaved (IFDMA) and localized (LFDMA).The Interleaved FDMA (IFDMA) is a distributed mode with equidistance between occupied subcarriers. In this paper, the PAPR for LFDMA and IFDMA techniques is simulated and compared. Simulation shows that the reduction of PAPR for IFDMA decreased more than 3 dB compared with LFDMA, which means that the IFDMA has better PAPR Performance than LFDMA. Moreover as shown as in the Figures there is a direct relationship between the Roll-off-factor (Alpha, α) and subcarriers, When the value of Alpha increases and the subcarriers increase, the result is a good performance of PAPR